Jellyfish aggregations and leatherback turtle foraging patterns in a temperate coastal environment - J Houghton; T Doyle; M Wilson; J Davenport; Graeme Hays (2006)
Leatherback turtles (Dermochelys coriacea) are obligate predators of gelatinous zooplankton. However, the spatial relationship between predator and prey remains poorly understood beyond sporadic and localized reports. To examine how jellyfish (Phylum Cnidaria: Orders Semaeostomeae and Rhizostomeae) might drive the broad-scale distribution of this wide ranging species, we employed aerial surveys to map jellyfish throughout a temperate coastal shelf area bordering the northeast Atlantic. Previously unknown, consistent aggregations of Rhizostoma octopus extending over tens of square kilometers were identified in distinct coastal “hotspots” during consecutive years (2003–2005). Examination of retrospective sightings data (>50 yr) suggested that 22.5% of leatherback distribution could be explained by these hotspots, with the inference that these coastal features may be sufficiently consistent in space and time to drive long-term foraging associations.